2023
DOI: 10.1111/imr.13252
|View full text |Cite
|
Sign up to set email alerts
|

Coengineering specificity, safety, and function into T cells for cancer immunotherapy

Greta Maria Paola Giordano Attianese,
Sarah Ash,
Melita Irving

Abstract: SummaryAdoptive T‐cell transfer (ACT) therapies, including of tumor infiltrating lymphocytes (TILs) and T cells gene‐modified to express either a T cell receptor (TCR) or a chimeric antigen receptor (CAR), have demonstrated clinical efficacy for a proportion of patients and cancer‐types. The field of ACT has been driven forward by the clinical success of CD19‐CAR therapy against various advanced B‐cell malignancies, including curative responses for some leukemia patients. However, relapse remains problematic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 473 publications
(836 reference statements)
0
3
0
Order By: Relevance
“…Investigating the spatial distribution of E3K CAR-T cells would provide information as to whether the observed effects are solely due to targeting of perivascular cells or whether the CAR-T cells also target CAFs positioned more distally from vascular structures. Further, characterization of the E3K CAR-T cells that have homed to the tumor will be important to determining whether they would benefit from next generation engineering, 50 such as ablating TGFBR2 to prevent T cell exhaustion in the transforming growth factor-β (TGF-β)-rich TME 51 or co-expressing IL-7 and CCL19 to enhance infiltration and survival. 52 In this study, E3K CAR-T cell target specific toxicity was observed in 4T1 tumor-bearing BALB/c mice whereas no toxicity was observed in tumor-bearing C57BL/6 or FVB/N mice treated with equivalent or greater doses of CAR-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the spatial distribution of E3K CAR-T cells would provide information as to whether the observed effects are solely due to targeting of perivascular cells or whether the CAR-T cells also target CAFs positioned more distally from vascular structures. Further, characterization of the E3K CAR-T cells that have homed to the tumor will be important to determining whether they would benefit from next generation engineering, 50 such as ablating TGFBR2 to prevent T cell exhaustion in the transforming growth factor-β (TGF-β)-rich TME 51 or co-expressing IL-7 and CCL19 to enhance infiltration and survival. 52 In this study, E3K CAR-T cell target specific toxicity was observed in 4T1 tumor-bearing BALB/c mice whereas no toxicity was observed in tumor-bearing C57BL/6 or FVB/N mice treated with equivalent or greater doses of CAR-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the highlighted genes might be used for modifying T cell function through co-engineering strategies, thus improving T cells’ metabolic fitness and augmenting tumor control of T cell therapies. 74 Finally, more data have to be collected in order to address potential links between blood-based metabolic biomarkers and the metabolic landscape of the TME. This could also include a possible connection between the predictive value of serum LDH levels, 75 , 76 , 77 , 78 , 79 and the secretion of lactate into the TME, which was discussed here as a plausible factor related to an acquired ICI-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive T-cell transfer (ACT) therapy involves the infusion of tumor-specific T cells into patients and ranges from tumor-infiltrating lymphocytes (TIL) to lymphocytes engineered with antigen receptors (chimeric antigen receptor or T-cell receptor (TCR)). 1–6 Optimizing ACT to treat patients with aggressive malignancies is an important undertaking, given that this treatment shows promise in the clinic. 7–10 In particular, lymphodepleting preconditioning regimens prior to ACT are standard modalities to enhance the potency of ACT and do so via multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%